2009
DOI: 10.4081/jlimnol.2009.146
|View full text |Cite
|
Sign up to set email alerts
|

Lago Maggiore oligotrophication as seen from the long-term evolution of its phytoplankton taxonomic size structure

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Electron microscopy showed that these spaces were filled with electron dense fibrillar structures or globules similar to polyphosphate bodies (Kom arek and Albertano, 1994). It is interesting to observe that another species e Tychonema sequanum e was identified by microscopic methods in Lake Maggiore (Kamenir and Morabito, 2009). This taxon, however, has smaller dimensions (2.5e5 mm width) compared to T. bourrellyi.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy showed that these spaces were filled with electron dense fibrillar structures or globules similar to polyphosphate bodies (Kom arek and Albertano, 1994). It is interesting to observe that another species e Tychonema sequanum e was identified by microscopic methods in Lake Maggiore (Kamenir and Morabito, 2009). This taxon, however, has smaller dimensions (2.5e5 mm width) compared to T. bourrellyi.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in B. longimanus releases rotifers, especially large C. hippocrepis colonies, from competition with cladocerans (Hovius et al 2006;Manca 2011). In Lago Maggiore, abundance and mean size of phytoplankton cells decreases with restoration (Manca & Ruggiu 1998;Kamenir & Morabito 2009). While microphagous species ingest multiple food items no larger than ~15-20 μm, raptorials prefer larger particles (Pourriot 1977;Karabin 1985;Wallace et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton body size is also related to ecosystem functioning as it affects the transfer of energy through the food web as zooplankton grazers specialise on different algal sizes (Jansson et al, 2007). Following a more functional approach, a phytoplankton assemblage can be described in terms of size spectra (Kamenir & Morabito, 2009) or Morpho-Functional Groups (Reynolds et al, 2002;Salmaso & Padisák, 2007).…”
Section: Compositionmentioning
confidence: 99%